Analysis of the Indonesian Vowel /e/ For Lip Synchronization Animation - Anung Rachman; Risanuri Hidayat; Hanung Adi Nugroho (IAES Indonesia Section, 2017)
Currently, voice recognition technology is widely used to produce lip sync animation. Vowels take the most dominant roles for lip sync animation as it always exists in every syllable. Therefore, it is necessary to select appropriate vowel traits for the system to be accurate. In general, there are five vowels of Indonesian language, namely /a/ /i/ /u/ /e/ and /o/. However, there are two vowels that contain several different tones: /o/ that are pronounced /o/ and /O/, and /e/ that are pronounced /e/, /ǝ/, and /ɛ/. The difference in tone can affect the accuracy of voice recognition on the lip sync animation system if it is not specified further. In this paper, the characteristic values of vowel /e/, /ǝ/, and /ɛ/ are compared and analyzed to find the significance of the difference. The sought characteristic values are the frequency of the formant (F1, F2, and F3) through the Praat software used to extract the features. Comparison is done using a statistical test of t-test. The results show that the three vowel tones /e/ have significant differences for all of F1 and most of F2